DEVELOPMENT OF MICROELEMENT-CONTAINING TECHNOLOGY NPK FERTILIZERS - Obidjonov D.O,; Zokirova N. R,; Erkaev A. U,; Nazirova R.M,; Kucharov B. K,; Zakirov B. S,; Yulbarsova M, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Considering the current negative balance of macroelements in the soil, the catastrophic decrease in humus content, the use of new generation agrochemicals is necessary to restore and increase fertility. Current trends in the development of world science in the field of mineral fertilizer technology are aimed at the urgent need to find new solutions in the field of agrochemical technology and the involvement of non-traditional raw materials.